HIGHER EDUCATION AND ECONOMIC GROWTH IN NORTH MACEDONIA: EVIDENCE FROM CAUSALITY TESTING AND COVID-19 CHALLENGES - Cvetanoska, Marijana; Trpeski, Predrag (Faculty of Economics-Skopje, SS. Cyril and Methodius University in Skopje, 2020)
The link between education and economic growth has been the subject of public debate, and it has been widespread interest among economists in solving key economic problems. As a determinant of human capital, which is one of the factors of production, education has its own contribution in the process of globalization where economies are transformed and based on knowledge. Particularly higher education has a high economic value because it causes the formation of human capital and it is often seen as vital for a continued growth performance, prosperity, and competitiveness in national and global economies. Higher education contributes to the economic growth by producing higher-level skills and competencies needed for a shift towards knowledge-based economy. For these reasons, countries all over the world especially the developing countries such as North Macedonia, are giving higher education special attention to facilitate the economic growth. In this study, the co-integration between higher education and economic growth in North Macedonia is analyzed using dynamic methods. Toda Yamamoto's approach for Granger's causality (TY) developed by Toda and Yamamoto (1995) is used to analyze the causality between economic growth and higher education. For this aim, a bivariate VAR model is constructed. This study provides an evidence for the causality between higher education and economic growth in North Macedonia. Moreover, a key role of higher education institutions is to drive innovation, with the aim of finding solutions to global challenges. Today, in response to the COVID-19 pandemic, there is a danger that COVID-19 will destabilize this educational level, with serious consequences. Therefore, the challenges that higher education is faced are emphasized in order to help education institutions and policy-makers to reflect on them and be prepared to address them, while re-emphasizing the role of higher education in supporting to conform the post-COVID-19 pandemic.
Keywords: economic growth; COVID-19; higher education; human capital; North Macedonia